Islam and Economic Welfare: The Role of Islamic Community Organizations in Realizing Community Economic Welfare - Olga Puspa; Didik Himmawan; Desi Rahayu Indraputri; Ahmad Khotibul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In the midst of the world economy, which continues to decline and gives rise to global poverty, it increasingly shows that the economic system that has been adopted so far is unable to provide solutions to prosperity and justice. In reality, one of the roots of the problem of poverty in many countries is being trapped by high debt. At the same time, the development of the Islamic economic system has actually become stronger and more proven in facing the global economic crisis. This research aims to find out the history of Islamic economics during the time of Umar bin Khattab, how Islamic organizations contributed to the economic welfare of society, and the development and role of sharia banking in the Indonesian economy. The analytical method used in this research is a quantitative analysis method (Quantitative Research) with a qualitative approach to library research (Library Research). The literature sources used are articles, journals, and holy verses from the Al-Qur'an. The results of the research show that during Umar's time, Baitu Mal had been established, which functioned as an institution handling state expenditure and income. It also served as a place to store the assets of the Muslims, and was further developed by Umar. The Islamic economic system forms the basis for applying everyday economics for individuals, families, community groups, and governments.